Phytostabilization of Arsenic in Soils with Plants of the Genus Atriplex Established in Situ in the Atacama Desert - Diaz-Schulze, O (Springer International Publishing, 2016)
In the ChiuChiu village (Atacama Desert, Chile), there is a high concentration of arsenic (As) in the soil due to natural causes related to the presence of volcanoes and geothermal activity. To compare the levels of As and the growth parameters among plants of the same genus, three species of plants were established in situ: Atriplex atacamensis (native of Chile), Atriplex halimus, and Atriplex nummularia. These soils have an As concentration of 131.2 ± 10.4 mg kg−1, a pH of 8.6 ± 0.1, and an electrical conductivity of 7.06 ± 2.37 dS m−1. Cuttings of Atriplex were transplanted and maintained for 5 months with periodic irrigation and without the addition of fertilizers. The sequential extraction of As indicated that the metalloid in these soils has a high bioavailability (38 %), which is attributed to the alkaline pH, low organic matter and Fe oxide content, and sandy texture. At day 90 of the assay, the As concentrations in the leaves of A. halimus (4.53 ± 1.14 mg kg−1) and A. nummularia (3.85 ± 0.64 mg kg−1) were significantly higher than that in A. atacamensis (2.46 ± 1.82 mg kg−1). However, the three species accumulated higher levels of As in their roots, indicating a phytostabilization capacity. At the end of the assay, A. halimus and A. nummularia generated 30 % more biomass than A. atacamensis without significant differences in the As levels in the leaves. Despite the difficult conditions in these soils, the establishment of plants of the genus Atriplex is a recommended strategy to generate a vegetative cover that prevents the metalloid from spreading in this arid area through the soil or by wind. © 2016, Springer International Publishing Switzerland.